Neurological Manifestations of Novel Coronavirus Disease in a 2-Month-Old Infant: A Case Report - Kamali Aghdam, Mojtaba; Bakhtiari, Hassan; Diaz, Diana Noemi; Eftekhari, Kambiz (Journal of Pediatric Neurology, 2020)
The main manifestations of novel coronavirus usually include fever and cough. Neurological manifestations have not been properly identified in children. A 65-day-old infant was hospitalized due to poor feeding, weakness, lethargy, and occasional cough. She suffered several seizures during her hospitalization. The brain computed tomography scan depicted a minor hemorrhage. Due to the exacerbation of her condition during hospital stay and the presence of respiratory symptoms in her parents, coronavirus disease was suspected. Reverse transcription–polymerase chain reaction (PCR) of coronavirus was positive for both: child and parents. In children with neurological manifestations such as lethargy, recurrent seizures, cerebral hemorrhage, and clinical evidence of respiratory symptoms in his/her relatives, PCR testing for coronavirus is recommended.
Keywords: infants; neurological symptoms; novel coronavirus